Maintenance of a female-limited colour polymorphism in the crab spider Synema globosum (Araneae: Thomisidae) - Ajuria Ibarra, Helena (2013)
The occurrence of multiple genetically and phenotypically distinct forms in a single interbreeding population, known as polymorphism, represents a long-standing puzzle in evolutionary biology. Several mechanisms, both selective and stochastic, have been proposed to account for the maintenance of such diversity. Nevertheless, although our knowledge about how these mechanisms might operate has increased substantially in recent years, the specific role that they play in the maintenance of polymorphisms in natural populations remains to be determined. In particular, negative frequency-dependent selection, where rare morphs have a fitness advantage over common morphs, has frequently been suggested to explain the occurrence of genetic variation, but conclusive evidence for its importance in natural populations has yet to be obtained. In this thesis, I investigated the maintenance of a female-limited colour polymorphism in the crab spider Synema globosum, and the role that negative frequency-dependent selection could have in this process. First, I described the natural history of S. globosum, which was previously unknown. Then, I looked at the nature of the colour polymorphism and investigated its mode of inheritence. Finally, I carried out a series of experiments to examine the potential role of negative frequency-dependent selection resulting from interactions with prey, and between potential mates, in the maintenance of the polymorphism. S. globosum was shown to be an abundant species in the study area and, apart from its striking polymorphism, it exhibits several interesting characteristics that would make it a useful model species for studies of behaviour, ecology, and evolution. The female morphs were shown to be discrete and genetically determined. No evidence for directional selection favouring one particular morph, or for geographic variation in selection, was found. Field experiments revealed an effect of a previous negative experience with a particular colour morph on subsequent responses of honeybees (Apis mellifera), one of S. globosum’s main prey, to the presence of spiders on flowers. This result provided support for the hypothesis that such interactions generate negative frequency-dependent selection. Similarly, mating experiments provided some evidence that reduced harassment of less frequently encountered female morphs by male S. globosum could also generate negative frequency-dependent selection. This work adds to a growing body research that has increased our understanding on the mechanisms that maintain diversity in nature and establishes the basis for future studies to investigate the exact ecological explanation for the observed phenotypic variation in S. globosum.